Controls on Asymmetric Rift Dynamics: Numerical Modeling of Strain Localization and Fault Evolution in the Kenya Rift. Issue 5 (10th May 2021) - Richter, Maximilian J. E. A.; Brune, Sascha; Riedl, Simon; Glerum, Anne; Neuharth, Derek; Strecker, Manfred R.
Abstract: Complex, time‐dependent, and asymmetric rift geometries are observed throughout the East African Rift System (EARS) and are well documented, for instance, in the Kenya Rift. To unravel asymmetric rifting processes in this region, we conduct 2D geodynamic models. We use the finite element software ASPECT employing visco‐plastic rheologies, mesh‐refinement, distributed random noise seeding, and a free surface. In contrast to many previous numerical modeling studies that aimed at understanding final rifted margin symmetry, we explicitly focus on initial rifting stages to assess geodynamic controls on strain localization and fault evolution. We thereby link to geological and geophysical observations from the Southern and Central Kenya Rift. Our models suggest a three‐stage early rift evolution that dynamically bridges previously inferred fault‐configuration phases of the eastern EARS branch: (1) accommodation of initial strain localization by a single border fault and flexure of the hanging‐wall crust, (2) faulting in the hanging‐wall and increasing upper‐crustal faulting in the rift‐basin center, and (3) loss of pronounced early stage asymmetry prior to basinward localization of deformation. This evolution may provide a template for understanding early extensional faulting in other branches of the East African Rift and in asymmetric rifts worldwide. By modifying the initial random noise distribution that approximates small‐scale tectonic inheritance, we show that a spectrum of first‐order fault configurations with variable symmetry can be produced in models with an otherwise identical setup. This approach sheds new light on along‐strike rift variability controls in active asymmetric rifts and proximal rifted margins. Key Points: 2D numerical models elucidate evolution of asymmetric Kenya Rift segments Intrabasinal faulting is caused by bending of the central block and does not reach the brittle‐ductile transition Small‐scale crustal inheritance can exert decisive control on first‐order rift architecture